The Poetics of Acculturation: A Case Study of Barzanji Recitation in the Religious Landscape of Indonesia - Khaerun Nisa Nuur; Marwah Limpo; Masykur Rauf (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
The persistence of religious literary practices in local Muslim communities remains underexplored, particularly in explaining how such traditions sustain social meaning, identity, and cultural adaptation in contemporary contexts. This study examines the practice of reciting the Barzanji book in Lapeo Village, Polewali Mandar Regency, Indonesia as a socio-religious phenomenon reflecting an ongoing process of acculturation between Arabic literary tradition and local Mandar culture. The research aims to explain the mechanisms underlying the sustained use of Arabic in Barzanji recitation and its role in shaping and reinforcing the community’s religious identity. An explanatory qualitative design was employed to capture the depth and complexity of the phenomenon. Data were collected through in depth interviews, participant observation, and documentation, and analyzed using thematic analysis guided by reception theory, lived religion perspective, and acculturation theory. The findings indicate that Arabic functions as a symbol of sacred authority, strengthening the perceived legitimacy and authenticity of the ritual. Collective recitation operates as a mechanism of social cohesion, fostering solidarity and shared religious sentiment. The incorporation of local material symbols reflects a contextual process of cultural interpretation and adaptation. Furthermore, Barzanji serves as a form of nonformal religious education that transmits moral exemplars associated with the Prophet Muhammad. Overall, the study demonstrates that Barzanji constitutes a living religious literary practice and a dynamic socio-symbolic mechanism of religious acculturation in constructing Mandar Muslim identity.